2019
DOI: 10.1155/2019/8159671
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Corn and Soybean with Group 15 (VLCFA Inhibitor) Herbicides Applied Preemergence

Abstract: Limited information exists on the efficacy of pethoxamid for annual grass and broadleaf control in corn and soybean in Ontario. A total of 10 field experiments (5 with corn and 5 with soybean) were conducted during 2015 to 2017 in Ontario, Canada, to compare the weed control efficacy of dimethenamid-P at 544 g·ai·ha−1, pethoxamid at 840 g·ai·ha−1, pyroxasulfone at 100 g·ai·ha−1, and S-metolachlor at 1050 g·ai·ha−1 applied preemergence (PRE). Reduced weed interference with pyroxasulfone and dimethenamid-P resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Although residual herbicide efficacy and selectivity is driven by a variety of factors (Prata et al 2003), our results are in agreement with those reported in several other published studies on corn or alfalfa production. For example, Soltani et al (2019) found that when used with corn, S-metolachlor at 1.05 kg ha −1 provided excellent control (>90%) of redroot pigweed and green foxtail, intermediate control (65%) of common lambsquarters, and poor control (12%) of common ragweed. Likewise, metribuzin at 0.21, 0.31, or 0.42 kg ha −1 was reported to provide at least 80% control of Amaranthus spp.…”
Section: Weed Controlmentioning
confidence: 99%
“…Although residual herbicide efficacy and selectivity is driven by a variety of factors (Prata et al 2003), our results are in agreement with those reported in several other published studies on corn or alfalfa production. For example, Soltani et al (2019) found that when used with corn, S-metolachlor at 1.05 kg ha −1 provided excellent control (>90%) of redroot pigweed and green foxtail, intermediate control (65%) of common lambsquarters, and poor control (12%) of common ragweed. Likewise, metribuzin at 0.21, 0.31, or 0.42 kg ha −1 was reported to provide at least 80% control of Amaranthus spp.…”
Section: Weed Controlmentioning
confidence: 99%
“…The mixture of tolpyralate þ atrazine with acetochlor, dimethenamid-p, flufenacet, pendimethalin, pyroxasulfone, or S-metolachlor reduced barnyardgrass density 75% to 92% and shoot dry biomass 97% to 99%; there was no variation between the grass herbicides tested (Table 6). In other studies, Fluttert et al (2022) Foxtail Species (Giant and Green Foxtails) Tolpyralate þ atrazine in a mixture or in combination with acetochlor, dimethenamid-p, flufenacet, pendimethalin, pyroxasulfone, or S-metolachlor controlled foxtail species 80% to 99% at (Soltani et al 2019). Additionally, the density of green foxtail was reduced 99%, 95%, and 95%; and shoot biomass was reduced 99%, 93%, and 97% with dimethenamid-p, pyroxasulfone, and S-metolachlor, respectively (Soltani et al 2019).…”
Section: Barnyardgrassmentioning
confidence: 95%
“…When S-metolachlor was in a preformulated mixture with atrazine + mesotrione, mesotrione + bicyclopyrone, atrazine, or atrazine + mesotrione + bicyclopyrone control of green pigweed improved from 45 to 55 to 68 to 76% at 8 WAA. In a study by Soltani et al (2019), control of redroot pigweed at 8 WAA in corn with S-metolachlor, dimethenamid-p, and pyroxasulfone was 96, 99, and 99% at rates of 1050, 544, and 100 g a.i. ha -1 respectively.…”
Section: Efficacy Of Preemergence Herbicidesmentioning
confidence: 99%
“…Dimethenamid-p, flumetsulam, saflufenacil/dimethenamid-p, S-metolachlor/atrazine/mesotrione, S-metolachlor/mesotrione/bicyclopyrone, pyroxasulfone, dicamba/atrazine, mesotrione + atrazine, isoxaflutole + atrazine, atrazine, S-metolachlor/atrazine/mesotrione/bicyclopyrone, S-metolachlor/atrazine, and mesotrione + rimsulfuron reduced green pigweed biomass similarly 56 to 93% at 8 WAA (Table 4). Soltani et al (2019) reported that, S-metolachlor, dimethenamid-p, and pyroxasulfone at rates of 1050, 544, and 100 g a.i. ha -1 , respectively, reduced redroot pigweed density and biomass to the extent that they were similar to the weed-free control at 8 WAA.…”
Section: Efficacy Of Preemergence Herbicidesmentioning
confidence: 99%